2020
DOI: 10.1007/s11228-020-00539-z
|View full text |Cite
|
Sign up to set email alerts
|

Regularity of the Minimum Time and of Viscosity Solutions of Degenerate Eikonal Equations via Generalized Lie Brackets

Abstract: In this paper we relax the current regularity theory for the eikonal equation by using the recent theory of set-valued iterated Lie brackets. We give sufficient conditions for small time local attainability of general, symmetric, nonlinear systems, which have as a consequence the Hölder regularity of the minimum time function in optimal control. We then apply such result to prove Hölder continuity of solutions of the Dirichlet boundary value problem for the eikonal equation with low regularity of the coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Therefore STLA is a way we approach the regularity of the minimum time function, which is the prototype of solutions of Dirichlet boundary value problems for the Hamilton Jacobi equation. For the connection, see for instance the recent paper by Bardi, Feleqi and the author [5]. It is then clear that what we derive here has precise consequences on that problem as well.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Therefore STLA is a way we approach the regularity of the minimum time function, which is the prototype of solutions of Dirichlet boundary value problems for the Hamilton Jacobi equation. For the connection, see for instance the recent paper by Bardi, Feleqi and the author [5]. It is then clear that what we derive here has precise consequences on that problem as well.…”
Section: Introductionmentioning
confidence: 53%
“…For attainability of a target different from a point we recall the papers by Bacciotti [1] in the case of targets of codimension 1 and the author [19] for manifolds of any dimension, possibly with a boundary. We mention Bardi-Falcone [3] who showed that Petrov condition is also necessary for local Lipschitz continuity of the minimum time function, while in [5] we derive necessary second order conditions. More recently the work by Krastanov and Quincampoix [9,10] pointed out the importance of the geometry of the target and studied higher order attainability of nonsmooth targets for affine systems with nontrivial drift.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Here, the dissipative rate γ is an increasing function taking values in ]0, +∞[ and ∂ P U (x) denotes the proximal subdifferential of U at x (see (6)). We call relation (5) the degree-k HJ dissipative inequality (where HJ stands for Hamilton-Jacobi).…”
Section: Introductionmentioning
confidence: 99%